Bibliometric Analysis of Islamic Banking Products in Encouraging the Finansial Inclusion in Indonesia - Hendra Ramadan; Joko Setyono (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
In order to determine how well Islamic financial products promote financial inclusion in the society, this study performed a bibliometric examination of the literature on Islamic finance and financial inclusion. The scholarly literature is analyzed for trends, patterns, and study focus using a bibliometric technique. Information gathered from 920 publications that were mentioned over 568,52 times between 2010 and 2024 demonstrates the literature's major contribution to the growth of the Islamic finance sector. While citation analysis identifies the subjects receiving the greatest attention in the literature, network visualization of research themes and trends shows the progression of ideas from theoretical to practical applications. These results offer a clearer picture of the growth of the Islamic financial sector and the obstacles in the way of achieving greater financial inclusion in society. By delving further into the patterns and trends seen in scholarly works, practitioners and policymakers may create more effective plans to increase public access to Islamic financial services while adhering to Islamic principles.